Evaluation of molecular typing for national surveillance of invasive clinical Haemophilus influenzae isolates from Denmark - Slotved, Hans-Christian; Johannesen, Thor Bech; Stegger, Marc; Fuursted, Kurt (Frontiers in Microbiology, 2022)
Haemophilus influenzae is a gram-negative coccobacillus known to cause respiratory and invasive infections. H. influenzae can possess a polysaccharide capsule that can be categorized into six different serotypes (Hia, Hib, Hic, Hid, Hie, and Hif), and non-encapsulated strains that are defined as non-typeable. H. influenzae can furthermore be characterized into eight biotypes (I–VIII). Traditionally, isolates have been serotyped and biotyped using phenotypic methods, however, these methods are not always reliable. In this study, we evaluate the use of whole-genome sequencing (WGS) for national surveillance and characterisation of clinical Danish H. influenzae isolates. In Denmark, all clinical invasive isolates between 2014 and 2021 have been serotyped using a traditional phenotypic latex agglutination test as well as in silico serotyped, using the in silico program “hinfluenzae_capsule_characterization” and the in silico program “hicap”, with the purpose of comparing the subsequent serotypes. Moreover, isolates were also biotyped usinga phenotypic enzyme test and the genomic data for detection of the genes encoding ornithine, tryptophan, and urease. The results showed a 99-100% concordance between the two genotypic approaches and the phenotypic serotyping, respectively. The biotyping showed a 95% concordance between genotyping and phenotyping. In conclusion, our results show that in a clinical surveillance setting in silico serotyping and WGS-based biotyping are a robust and reliable approach for typing clinical H. influenzae isolates.